2017
DOI: 10.1073/pnas.1703926114
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the frictional transition in shear-thickening suspensions

Abstract: Shear thickening in dense particulate suspensions was recently proposed to be driven by the activation of friction above an onset stress needed to overcome repulsive forces between particles. Testing this scenario represents a major challenge because classical rheological approaches do not provide access to the frictional properties of suspensions. Here we adopt a different strategy inspired by pressure-imposed configurations in granular flows that specifically gives access to this information. By investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
134
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(148 citation statements)
references
References 47 publications
14
134
0
Order By: Relevance
“…This jamming at lower values of ϕ in frictional systems is the result of the breakdown of lubrication and the onset of frictional contacts with the appearance of force chains as described in section 3.1 [Fernandez et al, 2013;Ness and Sun, 2016b;Wyart and Cates, 2014]. It is now understood that this process is fundamental to the rheology of hydrogranular flow and signals the onset of the so-called "boundary lubrication" frictional regime distinct from the "hydrodynamic" regime, where lubrication films are intact and particle friction plays almost no role [Bi et al, 2011;Clavaud et al, 2017;Fernandez et al, 2013;Grob et al, 2014;Mari et al, 2014]. A hydrogranular system in the hydrodynamic regime will jam at a value of ϕ = ϕ RCP , like that of frictionless systems.…”
Section: 1002/2017jb014218mentioning
confidence: 99%
See 2 more Smart Citations
“…This jamming at lower values of ϕ in frictional systems is the result of the breakdown of lubrication and the onset of frictional contacts with the appearance of force chains as described in section 3.1 [Fernandez et al, 2013;Ness and Sun, 2016b;Wyart and Cates, 2014]. It is now understood that this process is fundamental to the rheology of hydrogranular flow and signals the onset of the so-called "boundary lubrication" frictional regime distinct from the "hydrodynamic" regime, where lubrication films are intact and particle friction plays almost no role [Bi et al, 2011;Clavaud et al, 2017;Fernandez et al, 2013;Grob et al, 2014;Mari et al, 2014]. A hydrogranular system in the hydrodynamic regime will jam at a value of ϕ = ϕ RCP , like that of frictionless systems.…”
Section: 1002/2017jb014218mentioning
confidence: 99%
“…At large values of s, the so-called hydrodynamic regime, a fluid layer separates the two particle surfaces and so the bulk coefficient of friction depends on the value of s, not just the dry value of the particle-particle friction coefficient. However, when s ≪ 1, the system is in a contact frictional regime, the first normal stress difference is nonzero, and the bulk friction depends weakly on s and is described by the dry friction coefficient [Clavaud et al, 2017;Fernandez et al, 2013]. For geological applications we consider a roughness scale of δ rough = 1 μm.…”
Section: 1002/2017jb014218mentioning
confidence: 99%
See 1 more Smart Citation
“…While the shear-induced growth of particle clusters, referred to as "hydroclusters," has long been invoked to explain shear thickening, especially in Brownian suspensions of small colloidal particles [11,12], it was recently recognized that shear thickening involves solid friction activated through shear-induced compressive stresses, at least for non-Brownian particles [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The most recent success in the area has been the reproduction of the phenomenon of discontinuous shear thickening, the abrupt increase in the steady shear viscosity of a suspension when the shear rate is increased beyond some critical rate. It is now widely accepted that a key ingredient of the phenomenon is 'stress-induced friction' (Mari et al 2014;Wyart & Cates 2014), and this has been confirmed by experiment (Lin et al 2015;Clavaud et al 2017).…”
Section: Introductionmentioning
confidence: 88%